Emotions and Emotion Regulation in Indonesian Islamic Schools: A Qualitative Phenomenological Study of EFL Students’ Lived Experiences across Intercultural Contexts - Ariyanti Ariyanti; Sukaena Sukaena; Muhammad Bayu Pratama; Agnes Veronika; Fahrus Zaman Fadhly; Diana Rozelin (Dinamika Ilmu, 2026)
Emotions matter in English as a Foreign Language (EFL) learning because they shape how students participate, persist, and respond to classroom demands. Although emotion regulation has received growing attention in language education, little is known about how students in Indonesian Islamic schools describe and manage their emotions in everyday English lessons. This gap is important. When models developed mainly in Western psychological traditions are applied without cultural reading, students’ silence, hesitation, or restraint can easily be mistaken for low motivation or weak ability. In an Islamic-Indonesian school context, the same responses may also be connected with patience, modesty, face-saving, respect for others, or the wish to keep classroom harmony. Using a qualitative phenomenological design, this study explored the emotional experiences and emotion regulation strategies of 67 students from two Islamic high schools in East Kalimantan, Indonesia. Data were gathered through open-ended questionnaires and two focus group discussions involving 20 selected students, and were analysed thematically. The findings show three intertwined emotional patterns: enjoyment, confidence, and motivation; anxiety, confusion, boredom, and fear of making mistakes; and fluctuating or neutral emotional states. Students most often used cognitive reappraisal (n = 25) and expressive suppression (n = 13), but they also reported more practical strategies, including deep breathing, peer talk, goal reminders, resting, drawing, asking questions, and silent self-composure. These findings suggest that emotion regulation in Islamic EFL classrooms is not only an individual cognitive process. It is also embodied, social, and shaped by local cultural expectations. The study therefore calls for EFL classrooms where teachers read students’ silence and hesitation carefully, reduce the social risk of error, and support emotional well-being through culturally responsive pedagogy.